Strategi Marketing Public Relation NET. TV dalam Membangun Brand Awareness Melalui Aplikasi Netverse - Widya Lestari, Fanny; Kusumaningrum, Rastri; Mardiana, Flori (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Facing the development of digital technology, media companies such as TV stations in Indonesia are transforming by providing streaming services. Likewise, NET TV launched an Over the Top (OTT) platform called Netverse. In the midst of the popularity of OTT, companies must have the right strategy because of the intense competition with other OTT platforms that have been present first. This study aims to determine the marketing public relations strategy carried out by NET TV in building brand awareness through the Netverse application. This research uses planning theory by going through the stages of planning, implementation and evaluation, which cannot be separated from the concept of three ways strategy by Thomas L. Harris including pull, push, and pass. The method used is descriptive qualitative with data collection techniques in the form of interviews, observation, documentation and literature study. The results of this study indicate that NET's public relations strategy which utilizes media relations for publications, holds Net Goes to Campus events as a form of CSR, and community relations is quite successful in increasing Netverse downloader and viewer traffic. However, despite the increase, Netverse is still not at the top of mind stage so it still has to continue making efforts to expand Netverse's branding to the public.